Booklet Types of Macroscopic Fungi Riverbanks Nature Tourism Kembang River for Senior High School - Difa Pertiwi Krismadana; Sri Amintarti; Aulia Ajizah (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Media in biology learning is one of the means so that students understand the concept of biology in a broad sense. This encourages researchers to develop learning media in the form of macroscopic fungi booklets. This study aims to describe the characteristics and identify the types of macroscopic fungi found on the banks of the Kembang River natural tourism river and to describe the results of the validity of the macroscopic fungi booklet on the banks of the Kembang River natural tourism river as a learning medium for high school students. This research uses the descriptive method and 4D development method. The results showed that the characteristics of macroscopic fungi can be seen from the shape of the hood, the surface of the hood, its hymenophores, the shape of the stem, color, presence or absence of annulus and odor, and the type of substrate where the fungus grows. Macroscopic fungi found on the banks of the Sungai Kembang Nature Tourism river are divided by taxon level into 2 divisions, 3 classes, 4 orders, 6 familia, 8 genera, and 17 species. Utilization of research results on types of macroscopic fungi on the banks of the Kembang River natural tourism river is then presented in the form of a booklet (learning media) which gets an average expert validity of 82.10% with very valid criteria and suitable for use as a learning medium.Abstrak Media dalam pembelajaran Biologi merupakan salah satu sarana agar peserta didik memahami konsep pada Biologi secara luas. Hal tersebut mendorong peneliti untuk mengembangkan media pembelajaran berupa booklet materi jamur makroskopis. Penelitian ini bertujuan untuk mendeskripsikan karakteristik dan mengidentikasi jenis jamur makroskopis yang ditemukan di bantaran sungai wisata alam Sungai Kembang serta mendeskripsikan hasil validitas Booklet jamur makroskopis di bantaran sungai wisata alam Sungai Kembang sebagai media pembelajaran siswa SMA. Penelitian ini menggunakan metode deskriptif dan metode pengembangan model 4D. Hasil penelitian menunjukkan bahwa karakteristik jamur makroskopis dapat dilihat dari bentuk tudung, permukaan tudung, hymenophorenya, bentuk batang, warna, ada tidaknya annulus dan bau, serta jenis substrat tempat tumbuhnya jamur. Jamur makroskopis yang ditemukan di bantaran sungai Wisata Alam Sungai Kembang yang terbagi berdasarkan tingkatan taksonnya menjadi 2 divisio, 3 kelas, 4 Ordo, 6 Familia, 8 genus, dan 17 species. Pemanfaatan hasil penelitian jenis-jenis jamur makroskopis di bantaran sungai wisata alam Sungai Kembang kemudian disajikan dalam bentuk booklet (media pembelajaran) yang mendapat hasil rata-rata validitas ahli 82,10% dengan kriteria sangat valid dan layak digunakan sebagai salah satu media belajar.